Financial Management Standards For Bumdes Madalleng Cemba Village, Enrekang District - Rani Laela Anggraeni; Fitriani Fitriani (Journal AK-99, 2023)
The basic problem is that BUMDesMadalleng, Cemba has not been able to implement Village Accounting optimally because BUMDes officials consider that the reporting principles presented in Village Accounting are very complicated while the Human Resources they have in terms of financial management lack knowledge in terms of financial governance. Therefore, the goal to be achieved in this research is to find out the Financial Management Standards which can be used as a guideline for BUMDes in managing finances while still referring to SAK ETAP. The method used in this research is a qualitative approach. The results obtained in this study support that financial management at BUMDesMadallengCemba, Enrekang District can run well, a reporting format is needed that is easy to understand and can be carried out by BUMDes managers. The basic thing that needs to be understood by BUMDes managers in preparing Financial Reports can be following SAK ETAP, namely improving the pattern of recording cash flows both received and issued. The preparation of these Financial Management Standards is expected that BUMDes managers in the future will be able to improve their financial management so that the level of public trust is getting bigger and participatory goals are expected to run optimally